Linkage between stem colour and pigmentation in young leaves of castor: Linkage between stem colour and pigmentation in young leaves of castor - MANMODE DARPAN MOHANRAO,; S SENTHILVEL, (Journal of Oilseeds Research, 2020)
Development of superior cultivars in any crop including castor requires knowledge on inheritance of various traits to handle the segregating generations in various breeding methods. In the present study, inheritance of anthocyanin pigmentation in younger leaves was studied in three F2 populations. The results revealed that the presence of anthocyanin in emerging leaves inherited as monogenic dominant and it showed tight linkage with red stem colour.